Overview and critical survey of polyamide6 structural habits: Misconceptions and controversies. Issue 21 (2nd October 2020) - Seguela, Roland
Abstract: Various aspects of the structural habits and associated thermodynamic properties of polyamide6 are critically examined with regard to controversies that appeared in literature mainly due to misconceptions or erroneous/ambiguous interpretations of experimental findings. The structural habits under concern are the crystallization capabilities and chain topology, hydrogen bonds and sheet‐like structure, crystalline polymorphism together with thermodynamic stability. Thermo‐mechanical properties are also discussed for the sake of complementary argumentation. Comparisons are made with polycaprolactone, that is, the polyester homolog of polyamide6 regarding chain structure, in order to evaluate the actual role of the H‐bonds on the structural habits. Additional comparisons with polyethylene and polypropylene are also made at several occasions for the sake of supporting argumentation on the structural behavior of polyamide6. A temperature–time–transformation diagram of polyamide6 is finally proposed from the gathering of plentiful literature data. Abstract : The chain topology in semicrystalline polyamides should be of the kind of Fischer's solidification model involving profusion of long nonadjacent re‐entry chain loops together with numerous intercrystalline tie chains. This model can account for the low crystallinity of polyamides and their rather thin crystalline lamellae compared to polyolefins. It also enables to accommodate either parallel or antiparallel chains and the crystalline phase with chain folding in the amorphous phase in the case of melt‐crystallized polyamide6.